Associations between perceived racial discrimination, racial residential segregation, and cancer screening adherence among low-income African Americans: a multilevel, cross-sectional analysis. Issue 3 (3rd April 2023) - Ibekwe, Lynn N.; Fernández-Esquer, Maria Eugenia; Pruitt, Sandi L.; Ranjit, Nalini; Fernández, Maria E.
ABSTRACT: Objectives: African Americans suffer disproportionately from cancer compared to their White counterparts. Racism may be an important determinant, but the literature on its association with cancer screening is limited. We examine associations between racism and cancer screening among a sample of African Americans. Design: Guided by the Public Health Critical Race Praxis and the Behavioral Model of Health Services Use, we conducted a multilevel, cross-sectional study using cancer risk assessment data collected from 405 callers to the 2-1-1 Texas helpline. We merged these data with contextual data from the U.S. Census Bureau. We assessed perceived racial discrimination using the Experiences of Discrimination Scale and racial residential segregation using the Location Quotient for Racial Residential Segregation. We used multilevel regression models to test hypothesized associations between each indicator of racism and four cancer screening adherence outcomes (Pap test, mammography, colorectal cancer screening [CRCS], and any cancer screening). Results: Participants were 18–83 years old (mean = 45 years). Most (81%) were non-adherent to at least one recommended screening. Approximately 42% reported experiencing discrimination and 73% lived in a segregated neighborhood. Discrimination was non-significantly related to lower odds of mammography (aOR = 0 .68; 95%CI: 0.38-1.22), CRCS (aOR = 0 .79; 95%CI: 0.41-1.52), and any cancer screening adherence (aOR = 0 .88; 95%CI: 0.59-1.32). Segregation was related to greater odds of mammography (non-significant; aOR = 1 .43; 95%CI: 0.76-2.68) and CRCS (significant; aOR = 2 .80; 95%CI: 1.21-6.46) but not associated with any cancer screening. Neither indicator of racism was associated with Pap test screening adherence. Conclusions: Racism has a nuanced association with cancer screening among low-income, medically underserved African Americans. Specifically, discrimination appears to be associated with lower odds of screening, while segregation may be associated with higher odds of screening in certain situations. Future research is needed to better explicate relations between indicators of racism and cancer screening among African Americans.